Analysis Of Teachers’ Pedagogical Competence In The Planning, Implementation, And Evaluation Of Inclusive Learning At Mumtaz 1 Taman Elementary School - Moch Mafud Danni Ramadhan; Fakhrur Rozy; Ganal Arief Rahmawan (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2026)
This study focuses on the importance of teachers' teaching skills in implementing inclusive learning in elementary schools. Although inclusive learning has been implemented in many places, its implementation still faces obstacles in serving the diverse needs of students. This study aims to examine teachers' teaching skills in creating, implementing, and evaluating inclusive learning processes at Mumtaz 1 Taman Elementary School, as well as identifying problems and methods used in managing inclusive education. The researcher used a qualitative approach with a problem-solving research method. The subjects of this study were three: the first was a fifth-grade teacher, the second was the principal, and the third was a fifth-grade student with disabilities. Information was collected through observation, semi-structured interviews, and notes, then analyzed using interactive analysis and through information reduction, information presentation, and drawing conclusions using triangulation of sources and methods to ensure the validity of data and information. The results of this study indicate that teachers have improved their teaching skills in inclusive education through planning that begins with familiarizing students with comparison, effective communication and understanding student needs, as well as assessment that focuses on individual progress through evaluation, revision, and module deepening.